A new species of Eugenia (Myrteae, Myrtaceae) from the submontane forest of northern Atlantic Forest - Amorim, Bruno S.; Cabral, Fernanda N. (Phytotaxa, 2018)
Eugenia studerae is here described and illustrated. This species is restricted to submontane forests of northern Atlantic Forest and known only for the Alagoas state. Eugenia studerae is morphologically related to E. hirta. They share the small leaves, inflorescence with reduced main axis and subglobose and smooth fruits, but E. studerae differs by the inflorescence usually with 3–4 mature flowers/fruits, smaller and acute calyx lobes and the restricted distribution in submontane forests (vs. inflorescence usually with 1 mature flower/fruit, larger and rounded calyx lobes and the distribution in lowland coastal forests in E. hirta).